Reclaiming Eroded Soil Using Sawdust – Poultry Compost for Agricultural production - Dania, S. O.; Oason, V. O.; Anthony, J. A. (ADAN JOURNAL OF AGRICULTURE, 2024)
The removal of top soil with high organic matter content is a critical threat to soil functions in most tropical agricultural lands and compost can be utilized in build up of organic carbon stocks and the soil nutrient. A two - year experiment was conducted to evaluate the effect of different rates of compost application on soil properties, yield and nutrient uptake of maize in an eroded soil. The treatments: control, 5, 10, 15 and 20 tonnes per hectares (t ha-1) were laid out in Completely Randomized Design (CRD) and replicated thrice and data collected were statistically analysed. The soil was acidic and sandy in texture, the application of compost reduced the acidity and significantly (p < 0.05) increased organic matter and nutrient content of the soil. Maize grain yield of 3.08 and 2.56 t ha-1were obtained in 2015 and in residual experiment of 2016 respectively with the application of 20 t ha-1 of compost. In conclusion, the application of 20 t ha-1 of sawdust – poultry compost significantly (p < 0.05) improved the organic matter and nutrients status of the soil. Also, the yield and nutrient uptake of maize were significantly (p < 0.05) higher with the application of 20 t ha-1 of compost.